Linguistics: An introduction - Donna Jo Napoli (Oxford Univ. Press, 1996)
The book covers in depth the fice core areas of theoretical linguistics: phonetics, phonology, morphology, syntax, ans semantics; and adds brief discussions of conversation interaction and historical/comparative linguistics where appropriate.